2019
DOI: 10.1080/02134748.2018.1537650
|View full text |Cite
|
Sign up to set email alerts
|

The role of personal control in the palliative function of system justification among indigenous and non-indigenous Peruvian students / El rol del control personal en la función paliativa de la justificación del sistema entre la población indígena y no indígena de estudiantes peruanos

Abstract: In this article we propose a mediation model for the association between system justification and psychological well-being (i.e., the palliative function of ideology), based on system justification theory and compensatory control theory. Specifically, we argue that endorsing system-justifying beliefs leads to increased perceived personal control, which in turn predicts higher well-being. We used a convenience sample of students from two Peruvian universities. The results showed that system justification was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Although belongingness has long been known to contribute to psychological well-being (Baumeister & Leary, 1995;Townsend & McWhirter, 2005), its ability to transmit system-justifying beliefs into palliative benefits has been neglected in the literature. Indeed, research on the palliative effects of system-justifying beliefs typically focus on how system justification minimizes perceptions of discrimination (Bahamondes et al, 2019(Bahamondes et al, , 2020Suppes et al, 2019), increases perceived control (McCoy et al, 2013;Vargas-Salfate, 2019), or buffers the adverse effects of active harm (Harding & Sibley, 2013) and individual-based relative deprivation (Osborne & Sibley, 2013). Here, we show that belongingness also mediates the positive association between system justification and well-being.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although belongingness has long been known to contribute to psychological well-being (Baumeister & Leary, 1995;Townsend & McWhirter, 2005), its ability to transmit system-justifying beliefs into palliative benefits has been neglected in the literature. Indeed, research on the palliative effects of system-justifying beliefs typically focus on how system justification minimizes perceptions of discrimination (Bahamondes et al, 2019(Bahamondes et al, , 2020Suppes et al, 2019), increases perceived control (McCoy et al, 2013;Vargas-Salfate, 2019), or buffers the adverse effects of active harm (Harding & Sibley, 2013) and individual-based relative deprivation (Osborne & Sibley, 2013). Here, we show that belongingness also mediates the positive association between system justification and well-being.…”
Section: Discussionmentioning
confidence: 52%
“…Further research has shown that system-justifying beliefs confer palliative benefits (irrespective of group status, contrary to Jost and Hunyady's (2003) initial predictions) through diverse mechanisms. For instance, system justification increases well-being by (1) reducing the extent to which the disadvantaged see themselves (or their group) as targets of discrimination (Bahamondes, Gómez, Barrientos, Cárdenas, & Guzmán, 2020;Bahamondes, Sibley, & Osborne, 2019;Suppes, Napier, & Van der Toorn, 2019), (2) buffering the deleterious effect of interpersonal aggression (Harding & Sibley, 2013), (3) increasing personal control (McCoy, Wellman, Cosley, Saslow, & Epel, 2013;Vargas-Salfate, 2019) or perceived upward mobility (Li, Wu, & Kou, 2019), and/or (4) weakening the effect individual-based relative deprivation has on psychological distress and dissatisfaction with one's standard of living (Osborne & Sibley, 2013). Thus, the paths through which system-justifying beliefs confer palliative benefits seem to relate to overlooking a given form of inequality or negative experience in order to maintain positive views of the system (Jost & Hunyady, 2003;Lerner, 1980).…”
Section: Relational Needs and Their System-justifying Fulfilmentmentioning
confidence: 99%
“…System Justification. As the first dependent variable, we use system justification scale (Kay & Jost, 2003) as in Study 1, but adapted for Peru (Vargas-Salfate, 2019). This measure was highly reliable (α = .71).…”
Section: Methodsmentioning
confidence: 99%